Rocket and Groot : stranded on planet strip mall! - Angleberger, Tom (Angleberger, Tom. Rocket and Groot, 2016)
Stranded on a planet filled with dry cleaners, nail salons, and chain restaurants Rocket and Groot face killer robots bent on customer service and raccoon eating toilets.